7м-6м8дм + 3м9дм =

7м-6м8дм + 3м9дм =

  • 7м = 70 дм
    6 м 8ДМ = 68дм
    3м9дм = 39 дм
    70-68 + 39 = 41 дм = 4м1дм
    4дм4см = 44см
    2дм9см = 29см
    1дм9см19см
    44-29 + 19 = 34 см = 3 дм 4 см
    6м2дм = 62дм
    2м8дм = 28 дм
    3м5дм = 35дм
    62 дм + 28дм-35дм = 55дм-5м5дм
  • 1) 7м-6м8дм + 3м9дм = 70дм-68дм + 39дм = 41дм = 4м1дм
    2) = 44см-29см + 19см = 34см = 3дм4см
    3) = 602дм + 208дм-305дм = 505дм = 5м5дм

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *

73 − = 69